ANALISIS INVESTASI SAHAM DENGAN MENGGUNAKAN PRICE EARNING RATIO DAN PRICE TO BOOK VALUE PADA PERUSAHAAN INFOBANK15 YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2022–2024 - Bugis Setiawan; Ajeng Tita Nawangsari (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
The purpose of this study is to analyze the influence of the Price Earnings Ratio and Price to Book Value on stock investment decisions in companies included in the INFOBANK15 index listed on the Indonesia Stock Exchange for the 2022–2024 period. The study population includes all companies included in the INFOBANK15 index during that period. The research sample was determined using a purposive sampling technique and obtained nine companies as samples. Data collection techniques used financial report documentation and stock market data. Data analysis was carried out by calculating the intrinsic value of shares using the Price Earnings Ratio and Price to Book Value approaches, then compared with the current market price. The results show that based on the Price Earnings Ratio, all shares of the sample companies are in a fairvalued condition. Therefore, the recommended investment decision for investors is to hold off on purchasing shares until the share price better reflects their intrinsic value. Based on Price to Book Value, six companies namely BBNI, BBTN, BDMN, BJBR, BMRI, and BTPS are in an Undervalued condition, so the recommended investment decision for investors is to purchase shares of these companies, while three companies namely BBCA, BBRI, and BRIS are in an Overvalued condition, so the recommended investment decision for investors is to postpone purchasing shares until the market price is more in line with their intrinsic value.